Promoter-Terminator Gene Loops Affect Alternative 3′-End Processing in Yeast - Lamas-Maceiras, Mónica (J Biol Chem, 2016)
Many eukaryotic genes undergo alternative 3′-end poly(A)-site selection producing transcript isoforms with 3′-UTRs of different lengths and post-transcriptional fates. Gene loops are dynamic structures that juxtapose the 3′-ends of genes with their promoters. Several functions have been attributed to looping, including memory of recent transcriptional activity and polarity of transcription initiation. In this study, we investigated the relationship between gene loops and alternative poly(A)-site. Using the KlCYC1 gene of the yeast Kluyveromyces lactis, which includes a single promoter and two poly(A) sites separated by 394 nucleotides, we demonstrate in two yeast species the formation of alternative gene loops (L1 and L2) that juxtapose the KlCYC1 promoter with either proximal or distal 3′-end processing sites, resulting in the synthesis of short and long forms of KlCYC1 mRNA. Furthermore, synthesis of short and long mRNAs and formation of the L1 and L2 loops are growth phase-dependent. Chromatin immunoprecipitation experiments revealed that the Ssu72 RNA polymerase II carboxyl-terminal domain phosphatase, a critical determinant of looping, peaks in early log phase at the proximal poly(A) site, but as growth phase advances, it extends to the distal site. These results define a cause-and-effect relationship between gene loops and alternative poly(A) site selection that responds to different physiological signals manifested by RNA polymerase II carboxyl-terminal domain phosphorylation status.